Pembangkit Listrik Tenaga Surya untuk Energi Ramah Lingkungan yang Berkelanjutan - Fidelchristo Pijoh; Brahmana Duta Pratama Kusuma; Lasman Parulian Purba (Industrial & System Engineering Journals (ISEJOU), 2024)
This paper highlights the importance of Photovoltaic Solar Power Systems (SPP) in supporting sustainable energy. SPP converts sunlight into electricity, which not only reduces the carbon footprint but also enhances energy independence and supports environmental sustainability. Thus, this technology plays a crucial role in the transition towards green energy. Case studies in this journal demonstrate the significant contribution of SPP to green energy worldwide, showing how the implementation of SPP can reduce dependence on fossil fuels and minimize greenhouse gas emissions. The implementation of SPP in campus life is also a concern, where its application can create a more environmentally friendly and energy-independent environment. Integrating SPP into campus energy policies and infrastructure is a critical step to mitigating the impacts of climate change and ensuring a sustainable energy future. With proper development and application, SPP can become a major pillar in the global strategy to achieve long-term sustainability goals.